Uji toksisitas fraksi-fraksi etil asetat Rumput Mutiara (Hedyotis corymbosa L.) - Pince Salempa; Muharram Muharram; Muhammad Danial (Seminar Nasional LP2M UNM, 2019)
Plant Rumput Mutiara (Hedyotis corymbosa L.) is a species of the genus Hedyotis including Rubiacea family that has long been used by traditional communities for treatment.  This plant has the ability to cure ulcers, as antihepatotoxic which can protect the liver and treat the liver from damage or inflammation, and also has the potential as anti-cancer. Methods used included of ekstraction or maseration and bioactivity test ekstract with Brine Shrimp Lethality by using Artemia salina. From the result toxicity method Brine shrimp lethality test, the showed activity fraction ethyl asetat Rumput mutiara with each LC50 value 0.3389; 0.2609; 1.0853; 0.9372; 0.2609; 0.7655 µg mL-1.